How Does Green Marketing Claim Affect Brand Image, Perceived Value, and Purchase Decision? - Fatmawati Indah (EDP Sciences, 2021)
The rise of pro-environmental awareness has promoted a new innovative local brand that considers sustainable society life. This study analyses how the green marketing claim of new local cleaner products influences the brand image, perceived value, and consumer purchase decisions. The respondents of this study are consumers of local shoe cleaner products claimed as green ones. The setting is a new brand of shoe cleaner introduced in Yogyakarta, Indonesia. This brand is a green product developed with a green marketing program. Using the purposive sampling method, we chose one hundred fifty respondents. The data analysis is using Structural Equation Modelling (SEM) of AMOS 21. Our result shows that green marketing significantly impacts brand image, perceived value, and purchase decisions. Brand image and perceived value affect purchase decisions substantially.